Green Accounting Performance on Profitability on The Indonesian Stock Exchange - Darwin, Khadijah; Alimuddin; Nagu, Nadhirah; Madein, Afdal (Jurnal Aktiva : Riset Akuntansi dan Keuangan, 2024)
The aim of this research is to investigate and analyze the impact of green accounting and Kinerja Lingkungan on the profitability of food and beverage companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The sample, consisting of 8 companies, was determined using a purposive sampling method. The data utilized in this research comprise secondary data extracted from the annual reports of food and beverage companies listed on the Indonesia Stock Exchange (IDX) spanning the period 2018-2022. The analytical approach employed is panel data regression analysis, with the random effect model (REM) selected as the research model. According to the findings from the analysis conducted using Eviews (Econometric Views) version 12, it was discovered that the green accounting variable influences profitability. This is attributed to the perception of green accounting as a long-term investment for the company, wherein present expenditures can bolster the company's reputation. Conversely, the Kinerja Lingkungan variable does not impact profitability. Despite most companies receiving a blue rating, signifying compliance with environmental regulations, the results of Kinerja Lingkungan have not ensured an augmentation in the company's profitability.